Política económica internacional - Moral Bello, Cecilio (International Technical & Financial Institute (Madrid, España))
La obra recoge los aspectos más sobresalientes de la actual política económica nacional e internacional, con especial referencia a la política monetaria.

The book contains the highlights of the current national and international economic policy, with particular reference to monetary policy.
Libro de Investigación